1997
DOI: 10.1038/hdy.1997.11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic trade-off between early fecundity and longevity in Bactrocera Cucurbitae (Diptera: Tephritidae)

Abstract: The response to selection on age at reproduction was measured to test for a genetic trade-off between early fecundity and longevity in the melon fly Bactrocera cucurbitae (Coquillett). Three replicate lines were selected for propagation by breeding from young (Y-lines) and old (O-lines) adults, respectively. Selection was continued for 24 and 9 generations for Y-and O-lines, respectively. Females from O-lines lived longer than Y-line females as an indirect response to selection, indicating that longevity is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 40 publications
6
58
0
2
Order By: Relevance
“…Our results suggest that copulation itself can be costly, as suggested for other traits like ejaculate and sperm size (Dewsbury, 1982;Pitnick et al, 1995;Hosken, 2001). Other examples of genetic trade-offs have usually focused on females, but as with Hunt et al (2006) and our study, published work typically finds negative genetic correlations between reproductive effort (for example, fecundity) and longevity (for example, Zwaan et al, 1995;Miyatake, 1997).…”
Section: Male Mating Costssupporting
confidence: 66%
“…Our results suggest that copulation itself can be costly, as suggested for other traits like ejaculate and sperm size (Dewsbury, 1982;Pitnick et al, 1995;Hosken, 2001). Other examples of genetic trade-offs have usually focused on females, but as with Hunt et al (2006) and our study, published work typically finds negative genetic correlations between reproductive effort (for example, fecundity) and longevity (for example, Zwaan et al, 1995;Miyatake, 1997).…”
Section: Male Mating Costssupporting
confidence: 66%
“…In insects, circadian clocks, which rhythmically regulate most behavioural and metabolic processes, have been implicated in the regulation of life history traits such as pre-adult development time (Kyriacou et al, 1990;Paranjpe et al, 2005) and adult lifespan (Miyatake, 1997a;Klarsfeld and Rouyer, 1998). Correlation between development time and circadian clocks was also reported in laboratory selection studies on melon flies (Miyatake, 1997b;Shimizu et al, 1997) and fruit flies (Kumar et al, 2006;Takahashi et al, 2013;Yadav and Sharma, 2013a).…”
Section: Introductionmentioning
confidence: 92%
“…Populations selected for slower development and delayed reproduction showed increased pre-adult development time (Chippindale et al, 1994) and extended adult lifespan (Partridge and Fowler, 1992;Djawdan et al, 1996). While a study on the butterfly Bicyclus anynana reported a negative correlation between pre-adult development time and adult lifespan (Pijpe et al, 2006), others have reported positive [melon flies, Bactrocera cucurbitae (Miyatake, 1997a); D. melanogaster (Chippindale et al, 2004)] or no correlation [D. melanogaster (Zwaan et al, 1991)]. This suggests that correlation between pre-adult development and adult fitness traits depends on the selection protocol and/or the genetic architecture of the founder populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. cucurbitae strains were established by selecting for S and L development time from a massreared stock of B. cucurbitae (Mass) maintained at the Okinawa Prefectural Plant Protection Center, Okinawa, Japan (for a detailed description of the protocol see Miyatake, 1995;Miyatake and Shimizu, 1999). Two replicate 'young' and 'old' strains (Y1, Y2, O1 and O2) were also established from the base population by selecting for young and old age at reproduction (for a detailed description of the protocol see Miyatake, 1997bMiyatake, , 2002a.…”
Section: Cloning and Sequencingmentioning
confidence: 99%